Lymph Node Metastasis from Tall-Cell Thyroid Cancer Negative on 18F-FDG PET/CT and Detected by 18F-Choline PET/CT. (August 2015) - Piccardo, Arnoldo; Massollo, Michela; Bandelloni, Roberto; Arlandini, Anselmo; Foppiani, Luca
Abstract : Abstract: A 77-year-old woman underwent thyroidectomy and 131 I remnant ablation for tall-cell differentiated cancer (DTC) of the left lobe. Detectable Tg levels (4.1 μg/L) under TSH suppression, with undetectable serum Tg-antibody levels, prompted neck ultrasonography, which revealed a lymph node in the left laterocervical region and in the right retroclavicular region. 18 F-FDG PET/CT showed uptake by the left lymph node. 18 F-choline PET/CT showed increased uptake by both lymph nodes. Histopathology revealed DTC solid metastasis in the left lymph node and solid and cystic metastasis in the right one. 18 F-choline PET/CT can locate virulent DTC recurrence, thereby increasing 18 F-FDG PET/CT information.